Effectiveness of essential oils from Ngaoundere, against post-harvest insect and fungal pests of maize - Langsi, Dobgangha Jacob; Fokunang, Charles Ntungwen; Suh, Christopher; Agwanande, Ambindel Wilson; Tsatsop, Tsague Roli; Nukenine, Elias Nchiwan (Julius-Kühn-Archiv, 2018)
Successful storage of harvest is a matter of utmost importance in the Sudano-Guinean agro-ecological zone where intense cultivation takes place only once a year. Poor and rudimentary drying/storage methods, high relative humidity as well as inaccessibility to the chemical pesticides leave stored maize at the mercy of insect and fungal attack. Insect attack favours secondary attack by fungi; both leading to a fall in the nutritional, sanitary and organoleptic qualities of the stored maize. Thus, poor peasant farmers are left with the choice of locally available botanicals as alternatives to chemical pesticides. It is against this backdrop that this study seeks to determine the insecticidal efficacy of essential oils from the leaves of Chenopodium ambrosioides and Cupressus sempervirens together with their 50/50 binary combination against the maize weevil, Sitophilus zeamais, and the fungi: Rhizopus stolonifer and Aspergillus flavus on stored maize. Insect mortality and progeny inhibition and the inhibition of fungal invasion were evaluated. Pesticidal activities of both essential oils increased with ascending dose of application. 200 µL/kg of the binary combination caused 100% mortality within 14 days and it completely inhibited progeny production in the weevil. The mixture of the two oils showed additive effects against the weevils and fungi. The two essential oils in isolation significantly inhibited fungal spore invasion in 21 days of storage although A. flavus was less susceptible than R. stolonifer. Therefore both plants could provide active botanical pesticides against S. zeamais and fungal pests in stored maize.